PERLINDUNGAN HUKUM TERHADAP KREDITUR PENERIMA FIDUSIA AKIBAT OBJEK JAMINANNYA DISITA NEGARA MELALUI PUTUSAN PENGADILAN (Studi Putusan PT No. 315/PDT/2015/PT.MDN) - Muhammad Taufik Zas; Ida Nadirah; Bachtiar Simatupang (STAI Tapaktuan, 2020)
Fiduciary collateral is a guarantee for tangible and intangible movable objects given by the debtor to the creditor as the recipient of fiduciary collateral to guarantee repayment of the debtor's debt to the creditor in a loan agreement at the bank.The binding of fiduciary collateral results in the creditor having the preferred position of the fiduciary collateral object to execute the fiduciary collateral object in paying off the creditor's receivable.Confiscation of fiduciary collateral objects by the state through a court ruling that has permanent legal force because the debtor's mistake is not the responsibility of the creditor, and the creditor can file resistance (verzet) on the confiscation of the fiduciary collateral object. The results indicate that the implementation of a financing agreement with fiduciary collateral in a finance company PT. OTO MULTIARTHA is a customer obliged to fill out a loan application form completely by filling in his identity based on the data contained in the resident identification card and family card, the type of goods to be financed, the amount of the down payment, the installment period, the amount of installments each month, then the customer sign the application for credit and is also signed by the guarantor, both husband and wife, or the biological parent / guardian of the applicant.The legal status of the fiduciary collateral object which was confiscated by the state through a court decision related to criminal cases of conservation of biological natural resources and their ecosystems is the property of PT. Oto Multiartha and must be returned by the state through a court decision to PT. Oto Multiartha,because the debtor's debt has not been paid off and analysis of Medan District Court's Decision No. 315/PDT/2015/PT.MDN in the Case of Confiscation of Fiduciary Collateral Object in the form of a Car of Daihatsu Xenia which instructs to return the fiduciary security object in the form of 1 (one) unit car of Daihatsu Xenia is in accordance with applicable legal provisions under Articles 20 and 24 of Law No. 42 of 1999 concerning fiduciary collateral and also based on Article 194 and paragraph 6 of Article 195 of Criminal Code and Article 574 of Civil Code.